Pode ser mulher? Desafios no mercado de trabalho do agronegócio - Rigo, Vitória (2025)
This qualitative case study analyzed the perception of women who recently graduated in Agricultural Sciences regarding the difficulties faced in the Brazilian agribusiness job market. The research was conducted through the application of a structured questionnaire, with data interpreted through content analysis. The research, conducted with 27 women who graduated between 2000 and 2024, addresses barriers such as working hours, pay gap, prejudice, lack of opportunities and remuneration, as well as the difficulty in assuming leadership roles. The participants recommend persistence, personal appreciation, technical training, the search for knowledge and resilience. The importance of a support network among women, the balance between professional and personal life and the separation between these aspects are also highlighted.